Progress in modified carbon support materials for Pt and Pt-alloy cathode catalysts in polymer electrolyte membrane fuel cells - Wang, Yan-Jie; Fang, Baizeng; Li, Hui; Bi, Xiaotao T.; Wang, Haijiang (Progress in materials science, 2016)
H2-fed polymer electrolyte membrane fuel cells (PEMFCs) are the most advanced fuel cell technology to date and continue to be of great interest as prospective energy sources in numerous applications, including for low/zero-emission electric vehicles, distributed power generators in homes, and small portable electronic devices. However, the commercialization of PEMFC technology has been greatly hindered by certain challenges, mainly the sluggish kinetics of the oxygen reduction reaction at the cathode and the high cost of Pt-based cathode catalysts, the latter presently accounting for over 55% of the total PEMFC cost. To overcome the limited stability of state-of-the-art Pt/C, Pt and Pt-alloy catalysts supported on modified carbon materials have garnered significant interest in recent years. It is therefore timely to compile a review that focuses on Pt and Pt-alloy catalysts supported on modified carbon materials, examining their current R&D status, applications, challenges, and future prospects. This review provides a systematic and comprehensive survey of current Pt and Pt-alloy PEMFC cathode catalysts in terms of materials selection and design, synthesis methods, and structural features, emphasizing how these various aspects relate to the catalysts' physicochemical characterization and performance, and with the aim of shedding light on the future direction of PEMFC research.